Handedness and learning styles: a study of its inter relationship - Vijayan, Vineetha; Panchu, Pallavi; Bahuleyan, Biju (International Journal of Research in Medical Sciences, 2017)
Background: The alleged link between handedness and learning is debatable. Studies unveil that handedness has a way of influencing learning and affects the academic performance of students. Despite the researchers pointing out that handedness influences the brain organization and function, teaching strategies have largely ignored this fact. The concept of using various sensory modalities as a part of learning has not been comprehended well. The aim of the study is to find out the prevalence of handedness among our medical students and to look onto the types of learning styles amongst them and to determine the correlation between handedness with learning styles. Methods: A cross sectional study was conducted among hundred medical students using handgrip dynamometer for handedness and VARK questionnaire (Visual, auditory, read/write, kinesthetic; a validated tool that helps one to identify the most preferred sensory modality for learning) for determining the learning preference. Data was analysed using univariate and bivariate analysis through cross tabulation and Pearson chi square test using SPSS version 20. Results: Right handers preferred VARK with dominancy for auditory learning styles, left handers preferred VARK with dominancy for auditory and kinesthetic learning styles while ambidextrous prefer visual learning styles. Conclusions: The awareness of the association of handedness with various learning styles and its implications on academic performance should be at the forefront of teaching strategies adopted by teachers. Hence, we conclude that to be an effective learner, the learning needs have to be understood and cater to by the trainers.